Intellectual capital and financial returns of companies: A case study on industrial sector in Malaysia / Norlydawaty Hashim - Hashim, Norlydawaty (2007)
The purpose of this research is to investigate the association between the intellectual capital (IC) of industrial sector firms and their financial performance. The research use the Pulic's framework, has an Asian focus, and draws data from 90 publicly listed companies on the main board of Bursa Malaysia between years 2002 and 2005. In Pulic's framework, the Value Added Intellectual Coefficient (VAIC TM ) is used to measure the IC of companies. The VAIC TM method is designed to provide information about the value creation efficiency of tangible and intangible assets within a company. The method has the attraction of ease of data acquisition and the development of ratios from standard financial data available in company annual reports. The dependent variables are return on equity (ROE) and earnings per share (EPS) as the proxy to financial returns of companies. The independent variables are human capital efficiency (HCE), capital employed efficiency (CEE) and structural capital efficiency (SCE) as the proxy to the intellectual capital. It is empirical study using multiple regressions for the data analysis. The dependent variables EPS and ROE will be test sequentially using the regression model. IC is an area of interest to numerous parties, such as shareholders, institutional investors, scholars, policymakers, and managers. The findings will help to embolden modern day managers to better harness and manage IC. As a result, intellectual capital do associated with financial returns of industrial sector in Malaysia. Capital employed efficiency has greater influence on industry intensive sector compared to human capital efficiency. However, structural capital component shows insignificant result due to the characteristics of industrial sector itself, which needs more utilization on physical capital.